Doniecka szkoła prawa gospodarczego - zarys historii i koncepcji - Małecki, Witold (Studia Prawa Publicznego, 2023)
The Donetsk school of economic law began to emerge at the turn of the 1950s and 1960s in the Soviet Union, and then continued its activity after Ukraine gained independence in 1991. The Donetsk school of economic law presented the view on the legitimacy of separating economic law as an independent branch of law, whether in the conditions of the command economy or in the system of the market economy. During the period of socialism, the view on the independence of economic law was justiﬁed primarily by the speciﬁcity of the subject of regulation of economic law, which were social relations developing in the sector of the state socialist economy, with the participation of state economic organizations. After the collapse of the USSR and the adoption of the market economy system by Ukraine, economic law was distinguished on the basis of the speciﬁcity of its subject of regulation and the method of regulation. The subject of economic law regulation is economic activity, which is a manufacturing activity (production, performance of works and provision of services), and, at the same time, an activity consisting in organizing the use of assets. The method of regulating economic law involves combining the method of binding orders and the method of autonomous decisions by adjusting them to the needs of implementing the social economic order, based on ensuring the harmonization of public and private interests and guaranteeing partnership relations in the economy. Representatives of the Donetsk school of economic law played a dominant role in the preparation of the Economic Code of Ukraine (adopted in 2003), which comprehensively regulates the sphere of economic activity, covering both vertical and horizontal legal relations formed with the participation of economic entities.